1-(Phenylamino)Pseudo-Mauveine: A New Water Soluble Phenazine Dye. (July 2014) - Plater, M. John; Jackson, Toby
1-(Phenylamino)pseudo-mauveine was prepared by the oxidation of 1, 3, 5-tris(phenylamino)benzene and p -phenylenediamine with potassium dichromate. The absorption maximum of 535 nm is shifted hypsochromically by about 20 nm compared to that for pseudo-mauveine. Condensation of 1, 3, 5-tris(phenylamino)benzene with 4-nitrosodiphenylamine under strongly acidic conditions gave 1, 3, 7-tris(phenylamino)-5-phenylphenazinium sulfate and 10-phenyl-6, 8-bis(phenylamino)-2, 10-dihydrophenazin-2-one.